Asymptotics of normalized control with Markov switchings - Nikitin, A. V.; Khimka, U. T. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We study the process of transfer of Markov perturbations and control over this process under the condition of existence of the equilibrium point of the quality criterion. For this control, we construct a normalized process and establish its asymptotic normality in the form of the Ornstein – Uhlenbeck process in the case where the transfer process changes under the influence of Markov switchings along a new trajectory of evolution from the state in which it was at the time of switching.